Opinión pública contemporánea Otras posibilidades de comprensión e investigación - Cottet, Pablo (Social-ediciones, 2017)
This book is the result of five years of work by the Public Opinion Observatory of the University of Chile, of academics, academics and students who have studied how public opinion is studied, through a research nucleus. From there, beyond the nucleus, researchers were invited to participate in this illustrated location. The book, an echo of other contemporary sites of the social sciences and their conceptions of Public Opinion, has proposed an invitation: to recover the diversification, the leaks and transmutations of those ways of sharing, of communicating with opinions, what concerns us to communities as imagined as effective and pedestrian, as industrious as artisan, as officially produced as artisanal destabilizing.